1992
DOI: 10.1159/000170041
|View full text |Cite
|
Sign up to set email alerts
|

Net Ultrafiltration in Peritoneal Dialysis: Role of Direct Fluid Absorption into Peritoneal Tissue

Abstract: ‘Net ultrafiltration’ in peritoneal dialysis refers to the difference between the osmotically induced ultrafiltration into the peritoneal cavity and the fluid loss from the cavity during dialysis. Recent research has demonstrated that, during a 3- to 4-hour experimental dialysis, 5-25% of the total fluid loss is via lymphatics and the remaining fluid is absorbed directly into the tissue surrounding the peritoneal cavity. The driving force for this convection into tissue is the hydrostatic pressure gradient bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Scaling from 2,000 ml in a 70-kg human to a 275-g rat, the volume would be 41.4 ml, which produces similar intraperitoneal (ip) pressures to that observed in humans (5,12,27). The volume is completely absorbed in 18 -24 h. At no time after injection did the animal display any signs of distress with the use of this volume.…”
Section: Design Of the Animal Modelmentioning
confidence: 92%
“…Scaling from 2,000 ml in a 70-kg human to a 275-g rat, the volume would be 41.4 ml, which produces similar intraperitoneal (ip) pressures to that observed in humans (5,12,27). The volume is completely absorbed in 18 -24 h. At no time after injection did the animal display any signs of distress with the use of this volume.…”
Section: Design Of the Animal Modelmentioning
confidence: 92%
“…Briefly, we assume that the disappearance o f RISA from the peritoneal cavity is proportional to its con centration in dialysate (i.e. that RISA absorption is due to a bulk llow and that back diffusion is negligible [ 19,27]):…”
Section: Study Protocolmentioning
confidence: 99%
“…and (2) fluid absorption into tissues (due to hydrostatic pressure differences be tween the peritoneal cavity and the surround ing tissues). From the tissues, the fluid is absorbed into the capillaries due to the Star ling forces, whereas the macromolecules are absorbed slowly via local lymphatics [19,20].…”
Section: Relative Importance O F Lymphatic Absorption and Absorption mentioning
confidence: 99%
See 1 more Smart Citation
“…How can fluid be convected si multaneously in opposite directions? Some investigators have explained this paradox by assuming that any tracer found in the intersti tium is transported there by diffusion, while the majority of tracer and fluid leaves the peritoneal cavity together via the lymphatic system [9], However, protein transport stud ies provide strong evidence for significant convection of fluid (and tracer) through the interstitial pathway [10]. An alternative ex planation for this paradox is the nonuniform nature of the peritoneal 'membrane' (e.g., vis ceral vs. parietal, diaphragmatic vs. mesenter ic).…”
Section: Pathways For Fluid Loss From the Peritoneal Cavity During Pdmentioning
confidence: 99%